2011
DOI: 10.1002/chem.201001884
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinone‐Sensitized Photooxidation of 5‐Methylcytosine in DNA Leading to Piperidine‐Induced Efficient Strand Cleavage

Abstract: One-electron photooxidations of 5-methyl-2'-deoxycytidine (d(m)C) and 5-trideuteriomethyl-2'-deoxycytidine ([D(3)]d(m)C) by sensitization with anthraquinone (AQ) derivatives were investigated. Photoirradiation of an aerated aqueous solution containing d(m)C and anthraquinone 2-sulfonate (AQS) afforded 5-formyl-2'-deoxycytidine (d(f)C) and 5-hydroxymethyl-2'-deoxycytidine (d(hm)C) in good yield through an initial one-electron oxidation process. The deuterium isotope effect on the AQS-sensitized photooxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Experiments showed that compound 196 could be successfully transformed into the deoxyuridine derived triazole 197 in yield of 72% via N-arylation with 1,2,4-triazole in the presence of phosphorus oxychloride and triethylamine, and compound 197 could be oxidated to give compounds with efficient strand cleavage in a DNA duplex (Scheme 85). This synthetic method provides useful strategy for the preparation of deoxyuridines containing triazole derivatives in good yields [270].…”
Section: N-arylation Of 124-triazole Ringmentioning
confidence: 99%
“…Experiments showed that compound 196 could be successfully transformed into the deoxyuridine derived triazole 197 in yield of 72% via N-arylation with 1,2,4-triazole in the presence of phosphorus oxychloride and triethylamine, and compound 197 could be oxidated to give compounds with efficient strand cleavage in a DNA duplex (Scheme 85). This synthetic method provides useful strategy for the preparation of deoxyuridines containing triazole derivatives in good yields [270].…”
Section: N-arylation Of 124-triazole Ringmentioning
confidence: 99%
“…It is well-known that the reactivity of pyrimidine bases with most ROS including singlet oxygen, superoxide anion radical and hydrogen peroxide, at the exception however of hydroxyl radical (HO • ) is quite inefficient 41 . In addition to HO • -mediated reactions, pyrimidine bases can be part of one-electron photosensitized oxidative reactions, as it was demonstrated for the epigenetic modification 5-methyl-2'-deoxycytidine 42,43 . Therefore, results…”
mentioning
confidence: 99%